Dual-targeting peptides@PMO, a mimetic to the pro-apoptotic protein Smac/DIABLO for selective activation of apoptosis in cancer cells - Di Giorgio, Eros; Ferino, Annalisa; Huang, Weizhe; Simonetti, Sigrid; Xodo, Luigi; De Marco, Rossella (Frontiers in Pharmacology, 2023)
The refractoriness of tumor cells to apoptosis represents the main mechanism of resistance to chemotherapy. SMAC/Diablo mimetics proved to be effective in overcoming cancer-acquired resistance to apoptosis as a consequence of over-expression of the anti-apoptotic proteins XIAP, cIAP1, cIAP2. In this work, we describe a dual targeting peptide capable of selectively activating apoptosis in cancer cells. The complex consists of a fluorescent periodic mesoporous organosilicate nanoparticles that carries the short sequences of SMAC/Diablo bond with the v3-integrin ligand SMAC/Diablo bound the v3-integrin ligand. The dual-targeting peptide@PMO shows significant higher toxicity in v3 positive HeLa cells in respect to with respect tov3 negative Ht29 cells. @PMO exhibited synergistic effects in combination with Oxaliplatin in a panel of v3 positive cancer cells, while its toxicity is overcome by XIAP over-expression or integrin 3 silencing. The successful uptake of the molecule by v3 positive cells makes @PMO promising for the re-sensitization to apoptosis of many cancer types.